Analisis Tingkat Pengembalian Investasi Pendidikan pada Lulusan Jurusan Pendidikan Bahasa Inggris (Studi pada Perguruan Tinggi di Provinsi Jawa Barat dan Banten) - Devika Putri Kistiani, Devika (2020)
The rate of return on investment in education is the return of benefits to individuals who invest in education. The purpose of this research is to know and analyze how the return on investment in education and the results of the analysis of human resource investment using the Payback Period and Net Benefit or Cost Ratio methods for graduates majoring in English Education Department of Higher Education at West Java and Banten Provinces. The method used in this research is descriptive quantitative method. The population in this research were all graduates in the English Education Department at LLDIKTI Region IV with a sample of 54 graduates. The result of this research is that there is a difference in income between graduates domiciled in West Java and graduates domiciled in Banten. This is due to differences in employment and wage levels in each province. The results of the analysis of human resource investment using the Payback Period and Net Benefit or Cost Ratio methods showed that the investment made by graduates in the English education department of higher education at West Java and Banten is considered feasible. This means that the investment made is feasible to be an option. Because the education program is able to provide benefits or benefits to its graduates. So, it is necessary to maintain the English education department, especially universities in West Java and Banten. In addition, quality improvement must be carried out to provide high bargaining power for individuals to be able to compete for jobs. Keywords: Cost and Benefit Analysis, Feasibility of Education, Human Capital Investment, Rate of Return on Investment in Education.